Sounds Like Chicken : Sensory Marketing and Sound Effects - Yeoh, Joanne P.S.; Allan, David (Indian Journal of Marketing, 2020)
Sensory marketing appeals to our senses (sight, hearing, smell, touch, and taste). What if you could combine sight, sound (effects), and taste all in one advertisement ? Would it be more effective at influencing consumer behavior than music ? This study was conducted in Malaysia and looked at the integration of sound effects into advertising to bridge the gap between the senses of sight, sound, and taste (Fried Chicken). The results demonstrated that sound effects influenced consumers’ beliefs and purchase intentions more than music or silence. This research closes the gap on whether advertisers should use sound effects, music, or silence. It is the next step in sensory marketing and invites new attention to the combination of senses in advertising strategy.